“INTEGRATING DIGITAL TOOLS AND PEDAGOGICAL STRATEGIES IN TEACHING DESCRIPTIVE GEOMETRY AND ENGINEERING GRAPHICS” - Shodiev Furqat Davranovich, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article investigates the integration of digital tools and modern pedagogical strategies in teaching “Descriptive Geometry and Engineering Graphics” at higher education institutions. The focus is on improving students’ theoretical knowledge, practical skills, and spatial reasoning through interactive teaching methods. The article discusses the role of computer-aided design (CAD) software, simulations, and visual aids in enhancing learning outcomes and preparing students for professional engineering environments.